2004
DOI: 10.1361/10599630418103
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum Oxide Coatings as Candidate Environmental Barriers

Abstract: Tantalum (Ta) oxide, due to its high-temperature capabilities and thermal expansion coefficient similar to silicon nitride, is a promising candidate for environmental barriers for silicon (Si) nitride-based ceramics. This paper focuses on the development of plasma-sprayed Ta oxide as an environmental barrier coating for silicon nitride. Using a D-optimal design of experiments, plasma-spray processing variables were optimized to maximize coating density. The effect of processing variables on coating thickness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Optimization of the parameters for plasma spraying tantalum oxide coatings with minimal porosity was reported elsewhere. 17 All of the coatings were applied to an as-fired surface that had been given a post-sinter oxidation treatment. All of the substrates (2.5 cm  2.5 cm  0.3 cm) were cleaned ultrasonically for 5 min in propanol prior to spraying.…”
Section: Methodsmentioning
confidence: 99%
“…Optimization of the parameters for plasma spraying tantalum oxide coatings with minimal porosity was reported elsewhere. 17 All of the coatings were applied to an as-fired surface that had been given a post-sinter oxidation treatment. All of the substrates (2.5 cm  2.5 cm  0.3 cm) were cleaned ultrasonically for 5 min in propanol prior to spraying.…”
Section: Methodsmentioning
confidence: 99%
“…Ta 2 O 5 is an important material because of its useful dielectric, optical, catalytic, and chemical properties. [2][3][4][5][6] Most current optical and dielectric applications make use of the amorphous form that has a dielectric constant (K) of B27, but it has been shown that the TiO 2 -stabilized high-temperature form (H-Ta 2 O 5 ) exhibits significantly enhanced values of dielectric constant (as high as K 5 280 at room temperature). [7][8][9] The exact mechanism(s) for enhancement of K in TiO 2 -modified Ta 2 O 5 is under investigation, and requires a better understanding of the structure and phase transformations in pure and TiO 2 -stabilized H-Ta 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Moldovan et al [181] have sprayed Ta 2 O 5 coatings that can be considered for environmental barrier applications. The as-sprayed coatings were approximately 97-98 % dense and were composed of the low-temperature polymorph, β-Ta 2 O 5 and some α-Ta 2 O 5 .…”
Section: Zirconiamentioning
confidence: 99%